(untitled) (World Economics and Finance Bulletin, 2024)
This article discusses the issues of increasing the efficiency of a trading company using digital marketing, in particular using Internet marketing tools such as search engine optimization, contextual advertising, Google Maps, social media promotion and E-mail marketing, as well as artificial intelligence and web analytics.